Thermoelectric properties of La7Mo7O30 sintered by reactive spark plasma sintering. Issue 8 (15th April 2023) - Giovannelli, F.; Sabarthes, E.; Delorme, F.
Abstract: In this work, spark plasma sintering of La2 Mo2 O9 powder was used to achieve dense ceramics of La7 Mo7 O30 and explore their thermoelectric properties. SPS sintering of La2 Mo2 O9 powder at 973 K for 10 min under 90 MPa leads to a bicoloured sample with white and black faces. XRD patterns of white and black faces are attributed to La2 Mo2 O9 and La7 Mo7 O30 phases, respectively. These experimental conditions allow observing the in-situ reduction of La2 Mo2 O9 during the SPS process. With a longer sintering time of 30 min, a ceramic of La7 Mo7 O30 is obtained. Its electrical conductivity exhibits a semiconducting behaviour and reaches a value of 1000 Sm -1 at 1000 K. The negative Seebeck coefficient show a n-type conduction in this phase. La7 Mo7 O30 exhibits a very low thermal conductivity, less than 1 Wm −1 K −1 from room temperature up to 1000 K, similar to the values reported for La2 Mo2 O9 . A figure of merit of 0.04 is reached at 1000 K.